Can Healthy Fetuses Show Facial Expressions of “Pain” or “Distress”? - Reissland, Nadja (Public Library of Science, 2013)
BACKGROUND: With advances of research on fetal behavioural development, the question of whether we can identify fetal facial expressions and determine their developmental progression, takes on greater importance. In this study we investigate longitudinally the increasing complexity of combinations of facial movements from 24 to 36 weeks gestation in a sample of healthy fetuses using frame-by-frame coding of 4-D ultrasound scans. The primary aim was to examine whether these complex facial movements coalesce into a recognisable facial expression of pain/distress. METHODOLOGY/FINDINGS: Fifteen fetuses (8 girls, 7 boys) were observed four times in the second and third trimester of pregnancy. Fetuses showed significant progress towards more complex facial expressions as gestational age increased. Statistical analysis of the facial movements making up a specific facial configuration namely “pain/distress” also demonstrates that this facial expression becomes significantly more complete as the fetus matures. CONCLUSIONS/SIGNIFICANCE: The study shows that one can determine the normal progression of fetal facial movements. Furthermore, our results suggest that healthy fetuses progress towards an increasingly complete pain/distress expression as they mature. We argue that this is an adaptive process which is beneficial to the fetus postnatally and has the potential to identify normal versus abnormal developmental pathways.